Síntese, caracterização e potencial uso como agente antifúngico de nanopartículas de dióxido de titânio - Michellotti, Michel Augusto Massambani (2019)
Titanium dioxide is extremely important because of its physical and chemical properties and different types of crystalline morphology (Anatase, Rutile and Broquita). It is currently used in the fields of science, environmental and energy. The nanoparticulate form has advantages or specificities, since this material achieves a more efficient relation between surface / volume, causing it to have a larger area of action mainly in the use of its photocatalytic properties. In this work the synthesis of the titanium dioxide nanoparticle was carried out using the Pechini method, varying the synthesis temperature in order to observe the changes in its morphology and physico-chemical properties. The nanoparticles (NPs) synthesized as well as the commercial titanium dioxide were characterized by X-ray diffraction (XRD) and morphologically by Scanning Electron Microscopy (SEM). Its ability to generate hydroxyl radicals was determined by Electron Spin Resonance (RSE). Since the Aspergillus niger fungus tends to develop in humid environments bringing harm to society and the environment, this work proposed the use of NPs as an antifungal agent. The antifungal activities of the materials were evaluated through the Minimum Inhibitory Concentration (MIC). The DRX showed that the obtained phase with a temperature of 400ºC is Anatase and presents a higher ratio surface / volume, the diameter of the smaller crystallite of 7.74nm, the other samples analyzed were crystallographically presented as Rutilo and its diameter of 34,89nm. The DLS of the TiO2A sample showed that the nanoparticles were in the diameter range of 60 to 120 nm. The experiments with RSE showed that this crystalline phase Anatase presents better photocatalytic characteristics than the other samples, since its relation surface / volume is bigger than the other samples. The CIM showed that Anatase sample obtained a more expressive result in the antifungal aspect where the concentration (750ug / ml) to eliminate the fungus was smaller than the other samples.